2007
DOI: 10.1186/1753-6561-1-s1-s99
|View full text |Cite
|
Sign up to set email alerts
|

A nonparametric regression-based linkage scan of rheumatoid factor-IgM using sib-pair squared sums and differences

Abstract: Parametric linkage methods for quantitative trait locus mapping require explicit specification of the probability model of the quantitative trait and hence can lead to misleading linkage inferences when the model assumptions are not valid. Ghosh and Majumder developed a nonparametric regression method based on kernel-smoothing for linkage mapping of quantitative trait locus using squared differences in trait values of independent sib pairs, which is relatively more robust than parametric methods with respect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…However, as pointed out by Yang et al [2007], analyzing quantitative traits in affected sib-pair study designs may lead to reduced evidence of linkage. Moreover, violations in probability distribution assumptions of the quantitative trait like normality or symmetry due to skewness or ascertainment bias can result in reduced power to detect linkage, and hence, nonparametric statistical methods may be more suitable under such scenarios [Ghosh et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as pointed out by Yang et al [2007], analyzing quantitative traits in affected sib-pair study designs may lead to reduced evidence of linkage. Moreover, violations in probability distribution assumptions of the quantitative trait like normality or symmetry due to skewness or ascertainment bias can result in reduced power to detect linkage, and hence, nonparametric statistical methods may be more suitable under such scenarios [Ghosh et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…In order to validate this hypothesis for a non-parametric regression method, Ghosh et al [2007] extended their earlier method using squared differences only [Ghosh and Majumder, 2000] to a combined nonparametric regression strategy incorporating both squared differences and squared sums. Based on the simulated data set, they found that there was indeed a substantial increase in power.…”
Section: Analyzing Quantitative Traitsmentioning
confidence: 96%
See 1 more Smart Citation